MENGGAGAS KURIKULUM MULOK TEROBOSAN BERBASIS KEARIFAN BUDAYA NUSANTARA (Rekonstruksi Pengalaman Sedulur Sikep Sukolilo, Pati, Jawa Tengah) - Said, Nur (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
Initiated by none other than education to defend humanity as a whole through physical and psychological dimensions. Therefore, education can not be reduced merely to deliver students a mere material satisfaction, while the value immersiaal as social, spiritual and transcendental. Therefore, the curriculum should be developed on the basis of social conditions, culture and history which is held up the process of education or it is called place-based education. This brief paper will try to indigenous community